KAJIAN STATUS MUTU AIR, INVENTARISASI SUMBER PENCEMAR DAN ALTERNATIF STRATEGI PENGENDALIAN PENCEMARAN SUNGAI BARABAI KABUPATEN HULU SUNGAI TENGAH - Yenny Eranova; Danang Biyatmoko; Mijani Rahman; Yusanto Nugroho (EnviroScienteae, 2022)
Barabai River is one of the rivers in Hulu Sungai Tengah District which is widely used by the surrounding community for household, agricultural and industrial activities. Community activities around the Barabai River certainly have an impact on the decline in river water quality because the waste produced generally goes directly to other environments without prior processing. This study aims to analyze the water quality status of the Barabai River, take an inventory of the potential sources of water pollution in the Barabai River and formulate alternative strategies for controlling water pollution in the Barabai River.   The research was located on the Barabai River along ± 43.2 km which started from Tanjung Village, Hantakan District, towards Jaranih Village, Pandawan Subdistrict, to Tabat Village, Labuan Amas Utara Subdistrict. The water quality status of the Barabai River was calculated using secondary data from the 2017-2020 river water quality monitoring results sourced from the Department of Environment and Transportation of Hulu Sungai Tengah District using the pollutant index method. Potential sources of pollutants in the Barabai River were inventoried based on domestic, industrial and agricultural activities around the monitoring point for water quality sampling by collecting secondary data and field survey results, then a map of the distribution of each water pollutant source was described using the Geographic Information System (GIS) application.  Alternative policy strategies for controlling pollution of the Barabai River were analyzed using the SWOT method based on the Regulation of the State Minister of the Environment Number 01 of 2010 concerning the management of water pollution control.            The results showed that in 2018 the water quality status of the Barabai River met the quality standards while in 2017, 2019 and 2020 the status of the water quality was lightly polluted with parameters that did not meet the quality standards, namely Total suspended solid (TSS), Dissolved Oxygen (DO), Biological Oxygen Demand (BOD) and Fecal Coli. Potential sources of pollutants in the Barabai River consisted of domestic pollutant sources originating from residential activities in the Barabai River area, potential sources of Pollution Point Source (Institutions) originating from ± 21 types of businesses /activities located in Hulu Sungai Tengah District and potential sources of Non-Point pollutants Source coming from agricultural activities of rice fields and plantation. Alternative policy strategies for controlling the pollution of the Barabai River can be done by adding water quality monitoring points in industrial areas, improving river water quality, raising public awareness of waste management through sustainable and targeted socialization, tightening supervision of compliance with business people, expanding coordination inter-agency, controlling waste entering rivers, determining the capacity of water pollutant loads, constructing a wastewater treatment plants (IPAL), carry out an inventory and identification of water pollutant sources based on the Regulation of the Minister of the Environment Number 01 of 2010, and stipulate a Regional Regulation on licensing for the disposal of wastewater to water sources.